Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To rewrite the logarithm [tex]\(\log_4\left(\frac{1}{16}mn^2\right)\)[/tex] as a sum or difference of logarithms, we must use logarithmic properties, such as the logarithm of a quotient and the logarithm of a product. Recall the following properties:
1. [tex]\(\log_b\left(\frac{A}{B}\right) = \log_b(A) - \log_b(B)\)[/tex]
2. [tex]\(\log_b(AB) = \log_b(A) + \log_b(B)\)[/tex]
3. [tex]\(\log_b(A^k) = k \log_b(A)\)[/tex]
Given [tex]\(\log_4\left(\frac{1}{16}mn^2\right)\)[/tex]:
### Step 1: Apply the Quotient Rule
[tex]\[ \log_4\left(\frac{1}{16}mn^2\right) = \log_4(1) - \log_4(16mn^2) \][/tex]
### Step 2: Evaluate [tex]\(\log_4(1)\)[/tex]
[tex]\[ \log_4(1) = 0 \quad \text{(since any number's logarithm of 1 is 0)} \][/tex]
So the expression simplifies to:
[tex]\[ 0 - \log_4(16mn^2) = -\log_4(16mn^2) \][/tex]
### Step 3: Use the Product Rule
[tex]\[ -\log_4(16mn^2) = -\left(\log_4(16) + \log_4(m) + \log_4(n^2)\right) \][/tex]
### Step 4: Simplify [tex]\(\log_4(16)\)[/tex] and [tex]\(\log_4(n^2)\)[/tex]
Notice that [tex]\(16 = 4^2\)[/tex], so:
[tex]\[ \log_4(16) = \log_4(4^2) = 2 \log_4(4) = 2 \cdot 1 = 2 \quad \text{(since } \log_4(4) = 1\text{)} \][/tex]
Now simplify [tex]\(\log_4(n^2)\)[/tex]:
[tex]\[ \log_4(n^2) = 2 \log_4(n) \][/tex]
### Step 5: Substitute the simplified terms back in
[tex]\[ -\left(\log_4(16) + \log_4(m) + \log_4(n^2)\right) = -(2 + \log_4(m) + 2 \log_4(n)) \][/tex]
### Step 6: Distribute the negative sign
[tex]\[ -(2 + \log_4(m) + 2 \log_4(n)) = -2 - \log_4(m) - 2 \log_4(n) \][/tex]
Thus, the simplified form of [tex]\(\log_4\left(\frac{1}{16}mn^2\right)\)[/tex] in terms of a sum or difference of logarithms is:
[tex]\[ -2 - \log_4(m) - 2 \log_4(n) \][/tex]
1. [tex]\(\log_b\left(\frac{A}{B}\right) = \log_b(A) - \log_b(B)\)[/tex]
2. [tex]\(\log_b(AB) = \log_b(A) + \log_b(B)\)[/tex]
3. [tex]\(\log_b(A^k) = k \log_b(A)\)[/tex]
Given [tex]\(\log_4\left(\frac{1}{16}mn^2\right)\)[/tex]:
### Step 1: Apply the Quotient Rule
[tex]\[ \log_4\left(\frac{1}{16}mn^2\right) = \log_4(1) - \log_4(16mn^2) \][/tex]
### Step 2: Evaluate [tex]\(\log_4(1)\)[/tex]
[tex]\[ \log_4(1) = 0 \quad \text{(since any number's logarithm of 1 is 0)} \][/tex]
So the expression simplifies to:
[tex]\[ 0 - \log_4(16mn^2) = -\log_4(16mn^2) \][/tex]
### Step 3: Use the Product Rule
[tex]\[ -\log_4(16mn^2) = -\left(\log_4(16) + \log_4(m) + \log_4(n^2)\right) \][/tex]
### Step 4: Simplify [tex]\(\log_4(16)\)[/tex] and [tex]\(\log_4(n^2)\)[/tex]
Notice that [tex]\(16 = 4^2\)[/tex], so:
[tex]\[ \log_4(16) = \log_4(4^2) = 2 \log_4(4) = 2 \cdot 1 = 2 \quad \text{(since } \log_4(4) = 1\text{)} \][/tex]
Now simplify [tex]\(\log_4(n^2)\)[/tex]:
[tex]\[ \log_4(n^2) = 2 \log_4(n) \][/tex]
### Step 5: Substitute the simplified terms back in
[tex]\[ -\left(\log_4(16) + \log_4(m) + \log_4(n^2)\right) = -(2 + \log_4(m) + 2 \log_4(n)) \][/tex]
### Step 6: Distribute the negative sign
[tex]\[ -(2 + \log_4(m) + 2 \log_4(n)) = -2 - \log_4(m) - 2 \log_4(n) \][/tex]
Thus, the simplified form of [tex]\(\log_4\left(\frac{1}{16}mn^2\right)\)[/tex] in terms of a sum or difference of logarithms is:
[tex]\[ -2 - \log_4(m) - 2 \log_4(n) \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.